Growth pro-poorness from an intertemporal perspective with an application to Indonesia, 1997-2007 - Florent Bresson; Jean-Yves Duclos; Flaviana Palmisano (Asian Development Bank Institute (ADBI), 2017)
The impact of growth on the distribution of income or consumption is regularly debated at both the scientific and policy levels. Within the micro-oriented literature dedicated to growth pro-poorness evaluation issues, the focus is specifically on the poverty impacts of growth. Considering a cross-sectional perspective for poverty measurement, early contributions have logically assessed these distributional effects in an anonymous fashion. But this means ignoring both the income dynamics and mobility impacts of growth. The paper extends the growth pro-poorness framework in two important ways. First, a longitudinal perspective is adopted which accounts independently for anonymous and mobility growth effects. Second, the paper's treatment of mobility encompasses both the gain of "mobility as equalizer" and the variability cost of poverty transiency. Several decompositions are introduced to evaluate the relative contribution of each of these effects on the pro-poorness of distributional changes. An empirical illustration is performed using Indonesian data for the period 1997-2007.
Keywords: D31; D63; I32; 330; growth pro-poorness; income mobility; intertemporal poverty; Indonesia